Probiotic modulation of the microbiota-gut-brain axis and behaviour in zebrafish - Borrelli, Luca (Sci Rep, 2016)
The gut microbiota plays a crucial role in the bi-directional gut–brain axis, a communication that integrates the gut and central nervous system (CNS) activities. Animal studies reveal that gut bacteria influence behaviour, Brain-Derived Neurotrophic Factor (BDNF) levels and serotonin metabolism. In the present study, we report for the first time an analysis of the microbiota–gut–brain axis in zebrafish (Danio rerio). After 28 days of dietary administration with the probiotic Lactobacillus rhamnosus IMC 501, we found differences in shoaling behaviour, brain expression levels of bdnf and of genes involved in serotonin signalling/metabolism between control and treated zebrafish group. In addition, in microbiota we found a significant increase of Firmicutes and a trending reduction of Proteobacteria. This study demonstrates that selected microbes can be used to modulate endogenous neuroactive molecules in zebrafish.